Diagnosis of impacts in area of installation of small hydroelectricin the municipality of Taquaruçu do Sul/RS - Queiroz, Rosemar; Peyrot, Caroline; Torchetto, Natieli Luiza; Patatt, Eduardo Ruwer; Koppe, Ezequiel (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Watersheds are characterized by presenting areas drained by a water body and its tributaries, where the dynamics of this water body is directly related to the topography, vegetation, soil type, rainfall and anthropogenic activities on the environment. Because of this, this paper aims to demonstrate the impacts generated by the presence of a small hydroelectric (PCH) tourist area and its surroundings, as well as some measures of recovery and stabilization of the area around the River Fortaleza, via case study of the use and land use in the municipality of South Taquaruçu / RS. Is for achievement was raised data fields through field visit, photographic survey and through Google Earth. Proposals to control the impacts on the river, and PCH generated by human occupation in the area, are deploying range permanent preservation area, slope stabilization and installation of bins in the area of tourism. Therefore, for an adequate management of a watershed is necessary the development of activities in balance with the environment, allowing the socioeconomic development of the people and respecting the carrying capacity of the ecosystem.